Robotic level II inferior vena cava thrombectomy for metastatic melanoma - Watson, Matthew J. (Urol Case Rep, 2019)
We report on a case of a 38-year-old female who presented with metastatic malignant melanoma of her right kidney with Level II tumor thrombus. This is the first ever presented case of a renal melanoma IVC tumor thrombus. Furthermore, in an effort to expand the surgical scope of minimally invasive and robotic surgery, we report management of this lesion as the first case of non-renal cell carcinoma IVC tumor thrombus treated with a robotic thrombectomy.